A content analysis of how 'normal' sports betting behaviour is represented in gambling advertising. (4th May 2018) - Lopez-Gonzalez, Hibai; Guerrero-Solé, Frederic; Griffiths, Mark D.
Abstract: The pervasiveness of sports betting marketing and advertising is arguably normalising betting behaviour among increasingly larger groups of population. In their adverts, bookmakers represent characters and situations that conventionalise betting and promote specific behaviours while ignoring others. The present study examined a sample of British and Spanish sports betting television adverts ( N  = 135) from 2014 to 2016 to understand how bettors and betting are being represented. Using content analysis, 31 different variables grouped into seven broad categories were assessed, including general information about the advert, the characters and situations represented, the identification of the characters with sports, the use of online betting, the co-representation of gambling along other risky behaviours such as eating junk food and drinking alcohol, the amount of money wagered, and other variables such as the representation of free bets, humour, and celebrities. The results showed a male-dominant betting representation with no interaction between women. Typically, bettors were depicted surrounded by people but isolated in their betting, emphasising the individual consumption practice that mobile betting promotes. In-play betting was observed in almost half of the adverts. A little empirical evidence indicates that betting while watching sport in betting adverts is associated with emotionally charged situations such as celebrations and/or alcohol drinking. Bettors were typically depicted staking small amounts of money with large potential returns, implying high risk bets. Overall, the study provides preliminary evidence in understanding the social representation of betting behaviour by bookmakers and critiques the problematic consequences of such representation from a public health perspective.